2020
DOI: 10.1177/2050312120901732
|View full text |Cite
|
Sign up to set email alerts
|

Positive aging benefits of home and community gardening activities: Older adults report enhanced self-esteem, productive endeavours, social engagement and exercise

Abstract: Objectives: This study examined relationships between home and community gardening and older adults’ self-reported psychosocial and physical well-being, attitudes to aging relative to gardening activities and benefits of membership to a gardening group. Methods: A survey addressing (a) demographic characteristics, (b) gardening interests and sentiments, (c) activities, (d) benefits, (e) self-rated health and quality of life and (f) attitudes to aging was administered online and via mail-out. Results: Participa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
46
1
3

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 70 publications
(53 citation statements)
references
References 36 publications
3
46
1
3
Order By: Relevance
“…The rest were classified as 'no' (physically less active). This variable has been used in previous studies [6,21].…”
Section: Socio-demographic and Health-related Variablesmentioning
confidence: 99%
“…The rest were classified as 'no' (physically less active). This variable has been used in previous studies [6,21].…”
Section: Socio-demographic and Health-related Variablesmentioning
confidence: 99%
“…Walking or running in nature can result in less sadness [43], tension, confusion and anger [45], while cognitive capacity [47] as well as energy, such as vitality and enthusiasm, can increase [43,45]. Community gardening among the elderly [48] and children [49] can lead to physical and social benefits [50]. People visiting green spaces and having a stronger relatedness to nature more frequently experience better social cohesion [28], and activities in green spaces stimulate personal development, e.g., increased body appreciation [33].…”
Section: Nature Relatedness and Its Association With Wellbeing And Pementioning
confidence: 99%
“…Community gardening in the elderly [48] and children [49] can lead to physical and social benefits, but no differences in health and wellbeing can be found for the elderly compared to younger gardeners [50].…”
Section: Nature Relatedness and Its Impact On Wellbeingmentioning
confidence: 99%
See 1 more Smart Citation
“…22 Gardening and horticultural therapy have been shown to have positive psychological, social and physical benefits, and benefits are compounded when undertaken in groups. 30 Interestingly, in the study by MacAndrew et al, staff found that the walking programme enriched the lives of the participants, who were selected due to their wandering, and even created positive change in the walking and wandering habits of some participants. 19 While dementia is a cluster of incurable conditions, social participation and engaging in activities away from the RACF has the potential to prolong quality of life and potentially reduce behavioural symptoms in the care setting.…”
Section: Psychological Outcomesmentioning
confidence: 99%